Innovation capabilities and its impact on organizational readiness for change: An Analytical Research into The Automotive and Equipment Manufacturing State Company (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:                 The research aims to explore the impact of Innovation capabilities and their dimensions represented by (product Innovation capability, organizational Innovation capability process Innovation capability, marketing Innovation capability, Innovation resources, Innovation culture) in achieving organizational readiness for change in the company with its dimensions represented by (appropriateness, management support, change efficacy, personal beneficial). The researchers relied on the questionnaire as a tool to collect data and information from the sample of (150) respondents, which constitutes 83% of the population of (180) respondents from the departments of the Automotive and Equipment Manufacturing State Company, which included (general manager, assistant general manager, managers departments, division officials), and relying on the descriptive analytical approach, and the statistical program  (SPSS V.23) was used to calculate the arithmetic mean, standard deviation, coefficient of variation, relative importance, simple linear regression equation), and the most prominent results that the research reached are: the presence There is a significant impact of creative capabilities in achieving organizational readiness for change, and the more the surveyed company has an actual interest in applying the dimensions of creative capabilities to the product, process, and marketing, with the presence of a culture of creativity and the development of creative resources, this will have an effective and clear role in increasing the value of influence in achieving organizational readiness for change.